The effect of using of Folic acid as a food addivited to local Iraqi dose in milk ylied , body weight and some hematological traits - AL- Musodi, Mohaned F. Hussain (Journal of Kerbala for Agricultural Sciences, 2016)
The aim of this study was to investigate the effect of adding folic acid in two level to diet in some haemologicaltraits,milk yelid and body weight of local black dose, this study was conducted in private farm in Karbala city between 17/1/2015 to 21/6/2015,twenty one dose in 3-4 years old were divided randomly into three group (7each).Animal of first group (control) free from any addition only concentrated diet,the 2nd group feeded on 8 miliigrams of folic acid add to each Kg diet as a food addivites,while the 3rd group feeded on 16 milli grams of nigella sativa add to each Kg diet ,the result revealed the following: Milk ylied in T1 &T2 groups was significantly increased( P<0.05) comparative with control .Hemoglobine concentration, Red blood cells count , White blood cells count was significantly improved (P<0.05) in the T1&T2 groups at last month of study comparative with control group study , while dose body weight was no significant different in spit of the numberous different between groups.